Genotypic differentiation in Butomus umbellatus (Butomaceae) using isozymes and random amplified polymorphic DNAs - Fernando, Danilo D.; Cass, David D. (Canadian Journal of Botany, 1996)
In clonal plants like Butomus umbellatus, pollination between ramets commonly leads to geitonogamy since even distant ramets may belong to a common genet. A prior knowledge as to which ramets are genotypically different is essential to establish a cross-pollination treatment. Ramets from three introduced populations of B. umbellatus in western Canada (Hatzic Lake, British Columbia; Sturgeon River, Alberta; St. Andrews, Manitoba) were analyzed using isozyme and random amplified polymorphic DNA (RAPD) markers. Protein electrophoresis failed to reveal any difference in the banding patterns of 150 ramets using 16 enzyme systems. However, 5 of the 16 RAPD primers used were helpful in revealing polymorphism in terms of fragment amplifications. Three genets were differentiated, i.e., two from Hatzic Lake and one from both Sturgeon River and St. Andrews. Since B. umbellatus is largely unexamined, our data also represent a preliminary contribution on the genetic organization of this colonizing clonal aquatic species. Keywords: Butomus umbellatus, isozyme, RAPD, clone, genet, ramet.